Metadiscourse features in contemporary Islamic Friday Sermons in English - Mahmood, Israa Ismaeel (2019)
In the Islamic society and even in the society at large, Friday sermon is an effective vehicle of shaping people behaviours and influencing their religious orientation. It is one of the strongest Islamic obligations which is hold weekly to disseminate and persuade people of certain ideology through preaching and teaching approaches. In Friday sermons, as a rhetorical religious genre, religious orators permanently try to convince the audience using different strategies and language devices such as metadiscourse. Metadiscourse is a rhetorical strategy used to obtain persuasive and communicative purposes as it helps writers (speakers) to engage their audience and guide their understanding of a text. To this end, the current study aimed at examining the status of the rhetorical devises of metadiscourse in the three themes (belief, practice, and spiritual) of Islamic Friday sermon delivered in English language. Put it in another way, to understand the engagement between the religious orators and the congregation in the language of the Friday sermon, this study intended to (i) inspect the types of metadiscourse markers and the extent to which metadiscourse markers are deployed in the Islamic Friday sermons; (ii) identify the functions of metadiscoures markers in the discourse of Friday sermons; and (iii) find out the distinction in the use of metadiscourse markers among the three themes of the selected sermons. To achieve the aims of this study, Hyland’s (2005) interpersonal model of metadiscourse was adapted and the concordance MonoConc Pro 2.2 was used to analyse metadiscourse devices that were deployed by thirty orators in thirty English Friday sermons (10 per theme) selected purposively from different resources, such as khutbahbank.org, MuslimMatters.org, and the sermons delivered by the instructors of Almaghrib institute. The findings suggested that metadiscourse is prolific in the Islamic Friday sermons discourse and the orators relied on interactional markers more than interactive markers. Engagement markers were the most frequently used metadiscourse marker. In terms of the interactional category, transitions were the most commonly used marker. Endophoric marker was the least frequent deployment by the orators. In terms of metadiscourse functions, the persuasive and communicative aspects of metadiscourse effectively supported the sermonic discourse purposes. According to the findings, the dominant presence of metadiscourse is in the sermons of practice/action theme. This shows the vital role of metadiscourse features in the sermons of teaching nature.